PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS 5 SDN KARANGANYAR GUNUNG 02 SEMARANG - Nunik Miftakul Jannah; Qoriati Mushafanah (Jurnal Bionatural, 2024)
This research aims to determine the influence resulting from the use of the Problem Based Learning (PBL) learning model on the creative thinking abilities of grade 5 students at SD N Karanganyar Gunung 02 Semarang. Research method used The research method used in this research is a Quasi Experimental method. This experimental research was carried out by providing treatment to two experimental groups with the same level of ability in the form of learning techniques and models. The population of this study were 5th grade students at SDN Karanganyar Gunung 2 Semarang. Thesample of this research was 28 grade 5 students. Data collection techniques were tests, interviews and documentation. Data analysis techniques are validation tests, reliability tests, normality tests, homogeneity tests, and T-tests. The results of the research showed that the PBL learning model can influence the ability to think creatively, where the use of the lecture learning model was obtained, the t-count was -8.363 > t-table of 0.684, and obtained a significance of 0.000 < 0.05. The results of this research show that a regression of 2,539 has a positive value. Meanwhile, for the use of the PBL learning model, the t-count was -4.968 > t-table of 0.684, and obtained a significance of 0.000 < 0.05. The results of this research show that a regression of 2,423 has a positive value. It can be concluded that the PBL model can have a positive influence on creative thinking abilities. The PBL model is more influential where it is shown that the t calculated lecture is smaller than the t calculated by the PBL model, namely – 4.968 > -8.363. So it can be concluded that using the PBL model can have more influence on students' creative thinking abilities.